Integrasi Kearifan Lokal Masyarakat Baduy Pada Bahan Ajar Tematik Kelas 4 Sekolah Dasar - Dwi Kurniasih; Andika Arisetyawan (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Elementary schools in Indonesia have been implementing the 2013 Curriculum by using thematic learning. Teaching material that integrated with values and cultures is really needed since considering the conservative role of the curriculum as a means of relevant values and culture and the evaluative role that supports the choice of values and culture that will be inherited. Local wisdoms have been chosen as an inheritage culture for generations. One of them is the Baduy community in Banten. Baduy is one of unique tribe living in harmony with nature and avoiding the life of the modern world. This research tried to explore how to integrate the local wisdom of the Baduy community into a thematic teaching material. Researchers used qualitative research with ethnographic design with case study method. The data were collected by the triangulation technique and were analyzed using the Spradley model. The result described that the values of the local wisdom of the Baduy community in the form of preserving nature, humility, and mutual cooperation can be integrated into teaching material with through product model. For the maximum results, it can be supported by lesson plan, media, and the teacher's ability to present the teaching materials.